2024
DOI: 10.1021/acsanm.3c05686
|View full text |Cite
|
Sign up to set email alerts
|

Thioflavin-T-Enhanced Fluorescence in Cerium Adenosine Triphosphate Coordination Polymer Nanoparticles for Selective and Sensitive Copper(II) Detection in E-Waste and Biological Samples

Sachin S. Kadlag,
Madhusudan Ghosh,
Prabhat K. Singh
et al.

Abstract: Coordination polymer nanoparticles (CPNs) are a unique class of nanoparticles designed via the self-aggregation of a metal ion and a polydentate ligand. Among them, lanthanide-based CPNs are considered to be the most promising due to their intrinsic luminescent properties, stability in different oxidation states, and high coordination flexibility. In the present study, cerium-based coordination polymer nanoparticles (Ce-CPNs) have been synthesized using adenosine triphosphate (ATP) as a cross-linking ligand. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 67 publications
1
0
1
Order By: Relevance
“…This indicated that the L3 ligand inhibited the continued size increase of Ab42-Cu 2+ aggregates. The control experiment with Ab42 without Cu 2+ (SI Figure S29A) showed much smaller aggregates than Ab42-Cu 2+ [54], further confirming the reported literature that Cu 2+ promotes the formation of larger non-amyloidogenic aggregates of Ab42 [52,53]. Ab42, when incubated with L3 in a 1:1 ratio in the absence of Cu 2+ , showed small aggregates like Ab42 incubated alone (SI Figure S29B).…”
Section: Effect Of L3 On Cu 2+ -Ab42 Aggregationsupporting
confidence: 86%
See 1 more Smart Citation
“…This indicated that the L3 ligand inhibited the continued size increase of Ab42-Cu 2+ aggregates. The control experiment with Ab42 without Cu 2+ (SI Figure S29A) showed much smaller aggregates than Ab42-Cu 2+ [54], further confirming the reported literature that Cu 2+ promotes the formation of larger non-amyloidogenic aggregates of Ab42 [52,53]. Ab42, when incubated with L3 in a 1:1 ratio in the absence of Cu 2+ , showed small aggregates like Ab42 incubated alone (SI Figure S29B).…”
Section: Effect Of L3 On Cu 2+ -Ab42 Aggregationsupporting
confidence: 86%
“…Our observations and fluorescent intensity values obtained for Ab42 agreed with this previous report. The size of the large aggregates we observed (17.3 µm 2 area) was much larger than the one reported (>1 µm) for Ab40 [52], while some others have reported large aggregates similar in size without Cu 2+ [53]. The sample with L3 added to Ab42-Cu 2+ during the initial incubation for 48 h, then used for microscopy 48 h after ThT addition, did not show large aggregates but smaller soluble aggregates (Figure 6B).…”
Section: Effect Of L3 On Cu 2+ -Ab42 Aggregationcontrasting
confidence: 61%